2021
DOI: 10.22201/ib.20078706e.2021.92.3437
|View full text |Cite
|
Sign up to set email alerts
|

Desarrollo estructural y composición florística arbórea en áreas afectadas por minería aurífera en la Amazonía peruana: a 20 años de su reforestación

Abstract: Desarrollo estructural y composición florística arbórea en áreas afectadas por minería aurífera en laAmazonía peruana: a 20 años de su reforestación Development of forest structure and tree floristic composition on affected gold mined sites in the Peruvian Amazon: 20 years after reforestation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 38 publications
3
7
2
1
Order By: Relevance
“…However, the expansion of deforestation and forest degradation in Madre de Dios persists [19,88], resulting in the emission of carbon into the atmosphere [16]. The mean AGB determined in 20-25 years of recovery, 198 ± 115 Mg ha −1 in areas of suction pumping mining and 45 ± 78 Mg ha −1 in areas recovering from heavy machinery mining in this study is less than the mean AGB reported for tropical Amazon forest from Madre de Dios (230-450 Mg ha −1 ) [39,86,89]. This suggests a more rapid recovery of AGB in suction pumping mining forest stands in comparison to those of heavy machinery, because >20-year-old suction pumping forest stands store similar amounts of carbon as naturally regenerating forests on abandoned deforested lands (secondary forests from non-mining impacts) of similar age [4,90].…”
Section: Recovery Of Agb Tree Diversity and Forest Structurecontrasting
confidence: 53%
See 4 more Smart Citations
“…However, the expansion of deforestation and forest degradation in Madre de Dios persists [19,88], resulting in the emission of carbon into the atmosphere [16]. The mean AGB determined in 20-25 years of recovery, 198 ± 115 Mg ha −1 in areas of suction pumping mining and 45 ± 78 Mg ha −1 in areas recovering from heavy machinery mining in this study is less than the mean AGB reported for tropical Amazon forest from Madre de Dios (230-450 Mg ha −1 ) [39,86,89]. This suggests a more rapid recovery of AGB in suction pumping mining forest stands in comparison to those of heavy machinery, because >20-year-old suction pumping forest stands store similar amounts of carbon as naturally regenerating forests on abandoned deforested lands (secondary forests from non-mining impacts) of similar age [4,90].…”
Section: Recovery Of Agb Tree Diversity and Forest Structurecontrasting
confidence: 53%
“…The lower similarity in species composition (<20% in higher successional stages, Table S3) across the chronosequence suggests a slower recovery compared to those of AGB, species diversity and forest structure. This pattern has been observed for other tropical forests [37] and in secondary forests after mining in the Peruvian Amazon [20,[39][40][41]. This highlights the need to promote active restoration strategies to establish both economically and ecologically important valuable native tree species [37].…”
Section: Tree Species Dominance and Compositionsupporting
confidence: 53%
See 3 more Smart Citations